Assessing Strategic Management Accounting Practices in Public Interest Companies in Malaysia - Nik Herda Nik Abdullah (Indonesian Journal of Economics, Social, and Humanities, 2020)
Strategic management accounting (SMA) practices play important roles in supporting decision making and strategic plan positioning in a firm. SMA practices comprise a range of useful and relevant techniques to facilitate a firm’s value. Through these techniques, a firm would be able to achieve competitive advantage and sustain economic growth, which leads to long-term performance. Recently, the role of SMA techniques in enhancing business performance has become the focus of many studies, unfortunately, studies that accessing the adoption of SMA practices in organizations particularly in Malaysia are not widely available. Hence, the purpose of this paper is to investigate the extent of SMA practices in public interest companies in Malaysia called Government Linked Companies (GLCs). Through SPSS analysis of data collected from 215 questionnaires, the study shows that top management of GLCs has a better understanding of SMA practices due to extensive use of SMA techniques which discovered from the findings and believe that it can benefit their organization. This paper has enriched the literature and provided an assessment of SMA practices for researchers and practitioners which can improve competitiveness in the industry, business prosperity, and secure long-term performance.